Pelatihan Analisis Permintaan dan Penetapan Harga Bagi Pengusaha Katering di Kabupaten Majalengka - Etty Zuliawati Zed; Berlian Lutfi Azizah; Elkya Najmi Kamila; Afifah Nur Hasna; Ayu Sulistiani (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Catering entrepreneurs in Indonesia have high market demand. Demand analysis and pricing training training is currently needed for small and medium-sized catering entrepreneurs to know to find out whether the demand is in accordance with the price that can compete in the market. Compete in the market. The utilization of this analysis aims to determine the number of potential customers that are considered important for market opportunities as well as assisting in improving efficiency and optimizing resource allocation. in improving efficiency and optimizing resource allocation. The method used used is a participatory approach to business actors including training and data collection. and data collection. This activity is implemented online through active communication and continuous mentoring. The main target that we took is catering businesses in Majalengka district. This activity includes: 1) Demand analysis training; 2) Pricing training; 3) Collection of questionnaire data collection; 4) Performance monitoring and evaluation. This activity is expected to can create opportunities for catering entrepreneurs in adapting to market dynamics ever-changing demand and can survive by having maximum profit and minimum cost. maximum profit and minimum cost.